The Development of Two-Tier Multiple Choice Test to Assess Studentsâ€™ Conceptual Understanding about Light and Optical Instruments (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2018)
This study aimed to develop a two-tier multiple choice test about the concept of â€œlight and optical instrumentsâ€ in 8th grade of Indonesian science curriculum. The test development procedure had three general steps: defining the content area of the test, identification on studentsâ€™ conceptions, and the development of two-tier multiple choice test. The final version of two-tier multiple choice test consisted of 25 items question. This test was administered to 95 junior high school students. The students had completed a unit on light and optical instruments. The reliability of the test was 0.76. Based on the data analysis, twenty-two alternative conceptions were identified. The results of the study showed that the two-tier multiple choice test was effective in determining the studentsâ€™ misconceptions and also it might be used as an alternative to the traditional multiple choice test. In conclusion, two-tier multiple choice test can be used to assess studentsâ€™ conceptual understanding as well as studentsâ€™ misconceptions on light and optical instruments concept.